Comparison of efficacy and safety of open and laparoscopic proximal ureterolithotomy for ureteral stone management: A systematic review and meta-analysis - Maliki, Ahmad; Fitriani, Rizka; Soebadi, Mohammad A.; Djatisoesanto, Wahjoe (Narra Sains Indonesia, 2024)
Despite advances in non-invasive and minimally invasive techniques, some proximal ureteral stones with impaction require open or laparoscopic surgery. No systematic reviews or meta-analyses have compared the efficacy and safety of open proximal ureterolithotomy and laparoscopic approaches. The aim of this study was to compare the efficacy and safety between open and laparoscopic proximal ureterolithotomy for ureteral stone management. Following the PRISMA guidelines, systematic searches were conducted in five databases (PubMed, Scopus, ScienceDirect, Web of Science, and ProQuest) to identify articles comparing those two surgical approaches. Operative time, blood loss, pain score, hospital stay, recovery time, and complications were collected and compared. Heterogeneity-based meta-analysis with random-effects or fixed-effects models were conducted. Two randomized controlled trials and four observational cohort studies with 386 participants met the criteria. Open surgery had significantly less time than laparoscopic ureterolithotomy (mean difference (MD): 26.63 minutes, 95%CI: 14.32, 38.94; p<0.0001). Intraoperative blood loss (MD: -1.27 ml; 95%CI: -6.64, 4.09; p=0.64) and overall complications (OR: 0.68; 95%CI: 0.41, 1.15; p=0.16) were not significantly different between two approaches. Laparoscopic ureterolithotomy reduced visual analogue scale (VAS) pain scores (MD: -2.53; 95%CI: -3.47, -2.03; p<0.00001), hospital stays (MD: -2.40 days; 95%CI: -3.42 to -1.38 days; p=0.03), and recovery time (MD: -9.67 days; 95%CI: -10.81 to -8.53 days; p<0.00001). In conclusion, open proximal ureterolithotomy had less time, but laparoscopic surgery reduced postoperative pain, hospital stay, and recovery time. Both methods had comparable intraoperative bleeding and complications.